Two new species of Kiekie Polotow & Brescovit, 2018 (Araneae: Ctenidae) from the highlands of Panama - Omelko, Mikhail M. (Zootaxa, 2023)
Two new species, Kiekie almae sp. n. and K. dietrichi sp. n. are described based on both sexes collected in highlands of Central America (Panama). Live males and females of both species were photographed in situ. A distribution map of all Panamanian Kiekie species is given based on new and literature-derived records.